Gender in the Amazonia and geospatial services - Irigoyen Alvizuri, Marina del Rosario (2022)
Review of Género en la Amazonía. Potencial de los Sistemas Geoespaciales para enfrentar las inequidades de género. Un estudio en el marco del Programa SERVIR-Amazonia. Twyman, J. & Acosta, M. (2022).  After taking a panoramic look at the status of the situation of gender relations in the Amazon, the study presents the limited experiences that boost geospatial services with a gender perspective, and concludes with recommendations on how to promote it.